Body-mass Index and Health - Emel Önal, Ayşe (IntechOpen, 2019)
The body mass index has an important place in weight control. Attention should be paid to the regularization of anthropometric measures and to physical activity to protect from increasing obesity that is associated with chronic noncommunicable conditions, such as diabetes mellitus, cancers and cardiovascular diseases. Also, attention should be paid to the countries that are developing. The daily intake of calories, carbohydrates, oils and proteins, fibers, vitamins and minerals and clean water is essential for all individuals, especially for children and for pregnant women.